Charge de travail et stress professionnel : deux facettes d’une même réalité ? - Sandrine Cazabat; Béatrice Barthe; Nadine Cascino (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article attempts to address the concepts of workload and job stress in a joint way, combining a psychosocial and ergonomic approach. This exploratory study was conducted among nurses in a Gerontology hospital. The objective was to learn why an increase in workload led to an increase in perceived stress levels and also whether nurses adopted a regulatory process based on social support. The Initial results show that the increase in perceived stress scores is associated with an increased number of work aspects considered stressful and a decrease in physical exertion. They show that the lowest stress scores appear when the nurses are provided with help in carrying out their tasks and when their work is not interrupted. Finally, the highest stress scores occur when nurses do not help each other. These results show evidence that the establishment of a regulatory process that is both adaptive and pathogenic. In order to handle a work overload, nurses isolated themselves in order to accomplish their duties and this isolation has an impact on their health.